Attic Fine Pottery of the Archaic to Hellenistic Periods in Phanagoria : Phanagoria Studies, Volume 1 - Morgan, Catherine (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
This book reviews the nature and social function of Attic fine pottery imported to the Greek colony of Phanagoria in the Taman Peninsula, southern Russia. The first part of the book reviews the history of research at Phanagoria, and presents a fully illustrated catalogue of Attic imports from the excavations of the Institute of Archaeology of the Russian Academy of Sciences (1971-1996) and latterly the University of London. A concluding section examines imports from the city and its cemeteries in the wider context of the Bosporan kingdom , drawing together a large collection of comparanda especially from the cities of the Taman Peninsula. Via comparison of data from Athens, the northern Aegean, Ionia, and the northern Black Sea, the changing role of Attic pottery in Black Sea trade is assessed.